(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
A descriptive study was conducted with 80 teachers in four primary and intermediate schools in the Al-Rassafa sector of Baghdad City from 2/9/2019 to 2/3/2020 to assess teachers’ knowledge about school violence and teachers’ responses towards intervention programs applied in schools’ violence prevention through a specific questionnaire constructed for the purposes of the study by the researcher and a review of literature. It consisted of 5 parts. The first part included personal data. The second Violence part included forms of the third violence. The third part included causes of school violence. The fourth part included intervention programs, and the sixth part concerned the source of information. Data was collected through the personal interview with the researcher. A descriptive statistical approach was used for data analysis by frequencies, percentages, and mean of score. Results of the study indicated that the majority of teachers have good knowledge about school violence related to its forms and causes, but some effective intervention programs cannot be applied when dealing with prevention and control. A higher percentage of sources of information was reported by using general information. Based on such results, the present study recommended that awareness programs and intervention strategies be designed and applied to the teachers, students, and parents about how to prevent violence in schools, as well as governmental or different social media, and comprehensive studies must focus on people, especially on school violence.